2004
DOI: 10.1002/bit.10856
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization and biocatalytic activity of fungal protease on gold nanoparticle‐loaded zeolite microspheres

Abstract: Gold nanoparticles are excellent biocompatible surfaces for the immobilization of enzymes. However, separation of the gold nanoparticle-enzyme bioconjugate material from the reaction medium is often difficult. In this study, we investigate the assembly of the gold nanoparticles on the surface of the amine-functionalized zeolite microspheres in the formation of zeolite-gold nanoparticle "core-shell" structures and, thereafter, the use of this structure in immobilization of fungal protease. The assembly of gold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 52 publications
2
28
0
Order By: Relevance
“…Enzymes entrapped inside nanoporous silica gel glass via both physical adsorption [33] and chemical binding [34] has the potentials to be applied in form of macrosize membranes and particles. More sophisticated structures, such as porous materials hosting enzyme-carrying nanoparticles [39] and cross-linked enzyme aggregates [40], have been developed by applying enzyme modification and fabrication procedures. In the later case, hierarchically ordered mesocellular mesoporous silica particles (200-500 nm), which have large mesocellular pores (37 nm) connected by mesoporous channels (13 nm), was used for the entrapment of cross-linked enzymes.…”
Section: Multi-scale Structured Biocatalystsmentioning
confidence: 99%
“…Enzymes entrapped inside nanoporous silica gel glass via both physical adsorption [33] and chemical binding [34] has the potentials to be applied in form of macrosize membranes and particles. More sophisticated structures, such as porous materials hosting enzyme-carrying nanoparticles [39] and cross-linked enzyme aggregates [40], have been developed by applying enzyme modification and fabrication procedures. In the later case, hierarchically ordered mesocellular mesoporous silica particles (200-500 nm), which have large mesocellular pores (37 nm) connected by mesoporous channels (13 nm), was used for the entrapment of cross-linked enzymes.…”
Section: Multi-scale Structured Biocatalystsmentioning
confidence: 99%
“…The biggest advantage of up to eight analyte by a measurement provides for a shorter time . In this study, the biotin-coated gold electrodes used with a layer of APTES (Davidson et al, 2004;Phadtare et al, 2004;Yakovleva et al, 2003), thus creating an amino surface with biotin-NHS match ends formed. On this layer and biotinylated streptavidin antibody (Milka et al, 2000) on the application of CRP measurement was carried out by applying the secondary antibody.…”
Section: Immunosensors Based Spr For Detection Of Crpmentioning
confidence: 99%
“…Stable covalent conjugation of a range of bioactive molecules such as enzymes (Phadtare et al 2004;Rossi et al 2004;Kuhn et al 2006Kuhn et al , 2007, mAbs (Tang et al 2005), peptides (Liu et al 2001), and DNA (Wang et al 2003;Zhang et al 2004) to the surface of NPs has been reported. Direct conjugation of ligands to the NP surface may overcome signifi cant obstacles inherent in the ubiquitous biotin-streptavidin system, including immunogenicity, increased molecular size (primarily due to the relatively large molecular mass of streptavidin), and limited in vivo application.…”
Section: Nanoparticle-based Therapeutic Systemsmentioning
confidence: 99%